EXPLORING HOW ELEMENTARY ENGLISH TEACHERS IN REGIONAL AREAS TRANSFORMED THEIR TEACHING DURING THE PANDEMIC - Susanto, Indra (Premise: Journal of English Education and Applied Linguistics, 2024)
The Covid-19 pandemic has brought about many changes in many spheres of life, including education. The country's unique geographic and demographic characteristics challenge Indonesia's government's remote learning policy to preserve education throughout the unprecedented period, including for English teachers in Indonesian regional areas. This study examines how elementary English teachers in regional Indonesia adapt their teaching throughout the pandemic. Through in-depth interviews, the experience of two elementary English teachers who taught before and during the epidemic was investigated in a qualitative study using a case study approach to determine how their teaching changed. The difficulties encountered and the help obtained were also examined. A thematic analysis of the interviews determined that the teaching transformation during the pandemic decreased, though to varying degrees, for each participant. The participants' difficulties contributed to the deterioration, for which the assistance they received was deemed valuable but insufficient. The study's findings indicate that regional English teachers in Indonesian regions request more institutional and governmental support for their teaching. Moreover, cooperation between several sectors is required to improve their education during and after the pandemic.